First Report of IgG4 Related Disease Primary Presenting as Vertebral Bone Marrow Lesions - van den Elshout-den Uyl, Debby; Spoto, Clothaire P. E.; de Boer, Mirthe; Leiner, Tim; Leavis, Helen L.; Leguit, Roos J. (Frontiers in Immunology, 2019)
IgG4 related disease is a fibro-inflammatory disorder characterized by swelling of tissues and affected organs accompanied by the development of scar tissue (fibrosis) and infiltration by IgG4 positive plasma cells. Almost any organ can be affected, but so far no reports of bone marrow involvement have been published. Here we present a case of a 76-year-old male with IgG4 related disease presenting primarily with vertebral bone marrow lesions. Histopathology showed the typical features of storiform fibrosis, and increased IgG4 positive plasma cells. Treatment with corticosteroids significantly improved wellbeing and resolved lesion size on MRI.